2000
DOI: 10.1177/02783640022068020
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Bilateral Teleoperation under Position and Rate Control

Abstract: A four-channel control architecture has been suggested in the literature to achieve transparency for master-slave teleoperator systems under position control. In this paper, the result is generalized to include teleoperator systems that are under rate control or more general master-slave kinematic correspondence laws, such as a mixedposition/rate mode. A one-degree-of-freedom example is given to outline the design and analysis of such a system for transparency and stability. The validity of the theory has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…According to [25], at low frequencies, near-transparency can be obtained by ignoring the inertial terms in the expressions for C 1 and C 4 in which case the original control design (12) is modified to …”
Section: Euclidean Distance Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [25], at low frequencies, near-transparency can be obtained by ignoring the inertial terms in the expressions for C 1 and C 4 in which case the original control design (12) is modified to …”
Section: Euclidean Distance Calculationmentioning
confidence: 99%
“…A complete discussion of the hybrid matrix analysis can be found in [14], [25]. In this representation, 11 12 21 22…”
Section: ) Frequency Domain Analysismentioning
confidence: 99%
“…In [6], a priori knowledge of the environmental inputs to the slave system is required to achieve the transparency control objective. Controllers aiming at low-frequency transparency were suggested in [9], [14], and [31]. Frequency-based control designs given in [6], [9], [10], [14], and [31] are for linear teleoperator systems.…”
Section: Introductionmentioning
confidence: 99%
“…Controllers aiming at low-frequency transparency were suggested in [9], [14], and [31]. Frequency-based control designs given in [6], [9], [10], [14], and [31] are for linear teleoperator systems. The concept of the four-channel architecture, which assumes knowledge of system impedances was introduced by the authors of [14] and [37].…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers demonstrated that transparency, as given in (3.1), can be achieved by a combination of controllers that satisfy (3.3), using 2 − 4 channels, [51], [100], [45].…”
Section: 1mentioning
confidence: 99%